Short Communication: Categorization models as a powerful tool in paleontological data analyses – the Phanerozoic bivalves - AHMED AWAD ABDELHADY; MOHAMMED MASOUD ABDALLA (Society for Indonesian Biodiversity, 2018)
Abdelhady AA, Abdalla MM. 2018. Short Communication: Categorization models as a powerful tool in paleontological data analyses – the Phanerozoic bivalves. Biodiversitas 19: 1769-1776. Predicting biotic responses to current and future global change can be acquired through understanding how biological and environmental traits shaped the past origination, dispersion and extinction patterns. A global dataset encompasses 161,357 taxon occurrences belonging to 2,378 bivalve genera from past and recent environments were analyzed based on the categorization model, a widely-used machine-learning analysis, using MS-SQL and Excel PowerView. The occurrence data was standardized using square-root transformation to downplay the effect of sampling effort. Thus, the examined traits are resulting from reliable ecological interactions. The results indicate that the biotic traits of the bivalve can be determined by the abiotic ones. Moreover, ecological traits such as life habit (i.e., infaunal vs. epifaunal), diet (suspension vs. deposit feeders, herbivores vs. carnivores), composition (aragonite vs. calcite), and locomotion (stationary vs. mobile) all exhibit significant relation to a specific environment. The results demonstrated that decision tree and association rules are primary powerful tools in analyzing huge biological data and in testing many useful bio-ecological hypotheses.